2012
DOI: 10.1039/c2jm15022k
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrogel pore-filled composite membranes with tunable and temperature-responsive size-selectivity

Abstract: Hydrogel pore-filled composite membranes (HPFCM) based on polyethylene terephthalate (PET) track-etched membranes with pore diameters between 200 and 5000 nm and temperature-responsive poly(N-isopropylacrylamide) (PNIPAAm) hydrogels were successfully prepared. A premodification of the pore walls by grafted linear PNIPAAm led to stable anchoring of crosslinked PNIPAAm prepared in a subsequent step. Proper tuning of photopolymerization conditions resulted in a desired microstructure of the hydrogels and thus tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
63
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 30 publications
(59 reference statements)
2
63
1
2
Order By: Relevance
“…[2,3] Eine Methode zur Synthese von porengefüllten kompositen "trackedetched" Poly(ethylenterephthalat)(PET)-Membranen wurde von Ulbricht und Mitarbeitern verçffentlicht. [4] Die Kompositmembranen wurden mittels In-situ-Photopolymerisation von Poly(N-isopropylacrylamid)(PNIPAAm)-Hydrogelen hergestellt und zeichneten sich durch temperaturabhängige Permeabilität sowie temperaturabhängigen Rückhalt aus. Hydrogel-beschichtete Membranen für die Wasserfiltration konnten La et al mittels Photopolymerisation von Poly(ethylenglycol)diacrylat (PEGDA) und einem funktionellen, Ammoniumsalz (RNH 3 Cl) enthaltenden Monomer herstellen.…”
unclassified
See 1 more Smart Citation
“…[2,3] Eine Methode zur Synthese von porengefüllten kompositen "trackedetched" Poly(ethylenterephthalat)(PET)-Membranen wurde von Ulbricht und Mitarbeitern verçffentlicht. [4] Die Kompositmembranen wurden mittels In-situ-Photopolymerisation von Poly(N-isopropylacrylamid)(PNIPAAm)-Hydrogelen hergestellt und zeichneten sich durch temperaturabhängige Permeabilität sowie temperaturabhängigen Rückhalt aus. Hydrogel-beschichtete Membranen für die Wasserfiltration konnten La et al mittels Photopolymerisation von Poly(ethylenglycol)diacrylat (PEGDA) und einem funktionellen, Ammoniumsalz (RNH 3 Cl) enthaltenden Monomer herstellen.…”
unclassified
“…Anzumerken ist jedoch, dass alle hier vorgestellten Membranmodifikationen mit Hydrogelen auf komplexen chemischen Verfahren basieren, beispielsweise auf der photoinitiierten "grafting from"-Polymerisation. [1][2][3][4][5][6][7] Die Realisierung von kontrollierten chemischen Reaktionen in der Tiefe der Membran oder der porçsen Stützstruktur stellt eine schwer zu lçsende Herausforderung dar.…”
unclassified
“…Besides our research, Abetz et al have employed polyvinylpyridine to fabricate pH-responsive membranes [25,26]. Wandera et al, Adrus et al and Yang et al employed poly(N-isopropylacrylamide) to prepare thermo-responsive membranes [17,19,27,28]. Hoare et al reported magnetically triggered nanocomposite membranes based on superparamagnetic nanoparticles [21].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, serious smart membranes have been reported to act in response to changes in electric fields [29] and ionic strength [30,31]. So far, the most popular strategy to fabricate stimuli-responsive membranes is to prepare copolymers of inherent stimuli-responsive properties [17,19,23,24,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation